Engine lubricating protective agent containing flake graphite and preparation method thereof

By adding scales to the engine lubricating protective agent to lubricating oil, combined with modified boron nitride, modified molybdenonate and decentralized medium, the problem of decline in lubricating oil performance and environmental pollution have been solved. Effect.

CN118931624BActive Publication Date: 2025-01-24JINBIDA (QINGDAO) NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410967224.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-18
Publication Date
2025-01-24
Estimated Expiration
2044-07-18

AI Technical Summary

Technical Problem

Lubricant in existing fuel vehicles has deteriorated performance during use and cannot meet the needs of efficient lubrication and environmentally friendly.

Method used

The engine lubricating protective agent with scale -containing graphite -containing graphite is used to form a lubricating protective agent by combining scales graphite with modified boron nitride, modified molybdenonate and decentralized medium. And environmental friendship.

Benefits of technology

Significantly improves the lubrication performance and environmental friendliness of the lubricating oil, extends the service life of the engine, reduces fuel and oil consumption, and reduces friction and wear.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118931624B_ABST
    Figure CN118931624B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of engine lubricating protective agents, and specifically to an engine lubricating protective agent containing flake graphite and a preparation method thereof, which is composed of the following raw materials: flake graphite, modified boron nitride, modified molybdate, a dispersion medium, a carbon deposit cleaning agent, an antioxidant and a viscosity index improver. In the present invention, flake graphite, modified boron nitride, modified molybdate and a dispersion medium have a synergistic effect, the mechanical support of the modified boron nitride carries the lamellar sliding structure of the flake graphite to form a continuous lubricating film, the smaller particle size and flaky structure of the flake graphite assist the continuous lubricating film to spread evenly on the surface of the modified boron nitride, the modified molybdate makes the continuous lubricating film stably adhere to the metal surface to form a protective film through physical and chemical effects, improves the fluidity of the engine lubricating oil and thus improves its heat conduction capacity, reduces the thermal damage to the metal surface, and the good solubility and suspension capacity of the dispersion medium further enhance the dispersibility and stability of the lubricating oil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of engine lubricating protective agents, in particular to an engine lubricating protective agent containing flake graphite and a preparation method thereof. Background Art

[0002] In fuel-powered vehicles, lubricants play a vital role, mainly including the following points: (1) Lubrication: Lubricants form an oil film between the various moving parts of the engine, reducing direct contact between metals, reducing friction, reducing wear, and helping the long-term operation of the engine; (2) Cooling: When the engine is working, the lubricant will take away some heat to help dissipate heat and prevent the engine from overheating; (3) Cleaning: The detergent components in the lubricant can remove metal debris, dust and other impurities inside the engine to prevent carbon deposits; (4) Anti-corrosion: Lubricants can prevent metal parts from oxidation and corrosion, thereby extending the service life of the engine.

[0003] As the development of the automobile industry enters the "post-fuel vehicle" era, companies that mainly produce lubricants and engine oils have also seen a slowdown in industrial upgrading iterations, but there are still a large number of fuel vehicles on the market, and these existing fuel vehicles urgently need to improve vehicle maintenance levels to meet various production and life needs. First, consider improving the performance of lubricants, because with the passage of time and changes in engine working conditions, the performance of lubricants will gradually decline and cannot maintain its initial freshness; secondly, consider enhancing the environmental friendliness of lubricants. Traditional petroleum-based lubricants will produce some harmful emissions when burned, which will affect the environment and cause potential pollution to the environment. Therefore, consider preparing an engine lubricant protective agent to enhance the lubrication performance and environmental friendliness of lubricants, improve engine power and reduce fuel and oil consumption, protect the engine by reducing wear and corrosion, improve the fluidity of lubricants, enhance heat dissipation performance, extend the service life of the engine, and meet the needs of environmentally friendly development. Summary of the invention

[0004] (1) Technical issues to be solved

[0005] The purpose of the present invention is to provide an engine lubricating protective agent containing flake graphite and a preparation method thereof, which is added to a plant base oil to enhance the lubricating performance and environmental friendliness of the lubricating oil, improve engine power and reduce fuel and oil consumption, protect the engine by reducing wear and corrosion, improve the fluidity of the lubricating oil and enhance the heat dissipation performance, extend the service life of the engine, and meet the needs of environmentally friendly green development.

[0006] (2) Technical solution

[0007] To achieve the above-mentioned purpose, on the one hand, the present invention provides an engine lubricating protective agent containing flake graphite, characterized in that it is composed of the following raw materials in parts by weight: 5 to 10 parts of flake graphite, 2 to 6 parts of modified molybdate, 4 to 8 parts of dispersion medium, 1 to 5 parts of carbon deposit cleaning agent, 2 to 8 parts of antioxidant, and 1 to 4 parts of viscosity index improver; the particle size of the flake graphite is 0.5 to 1 μm and the thickness is 20 to 50 nm; the surface of the modified molybdate contains long-chain alkyl and carboxylic acid groups.

[0008] Furthermore, the engine lubricating protective agent also includes:

[0009] Modified boron nitride;

[0010] The modified boron nitride and flake graphite are in a weight ratio of 5:(5-10);

[0011] The friction coefficient of the modified boron nitride is 0.1 to 0.15, and the specific resistance is 10 6 ~10 8 Ω·cm and the modified boron nitride surface contains siloxane groups.

[0012] Furthermore, the preparation method of the modified boron nitride comprises:

[0013] S11. Under ultrasonic conditions, boron nitride is added to an aqueous sodium hydroxide solution at an ultrasonic frequency of 40 to 50 kHz, and heated in a water bath at a heating temperature of 70 to 80° C. for a reaction time of 4 to 6 hours to obtain a first mixed solution;

[0014] S12. Adding silane coupling agent KH-570 and anhydrous ethanol to the first mixed solution in sequence under stirring, heating to 50 to 60° C., stirring for 3 to 4 hours until the reaction is sufficient to obtain a second mixed solution;

[0015] S13. The second mixed solution is allowed to stand for 8 to 10 hours, followed by solid-liquid separation, and the obtained precipitate is dried at a temperature of 90 to 120°C for 12 to 15 hours. After drying, it is vacuum calcined at a heating rate of 5 to 10°C / min, at a temperature of 400 to 500°C, and for 3 to 4 hours. The obtained solid is the modified boron nitride.

[0016] Furthermore, the preparation method of the modified molybdate comprises:

[0017] S21. While stirring, add molybdic acid (H2MoO4) to anhydrous ethanol and stir for 1 to 2 hours to fully dissolve it. Heat it to 80 to 100°C in a water bath and then add concentrated sulfuric acid (98% H2SO4) and octanol (C8H 17 OH) for esterification reaction for 8 to 10 hours to obtain a third mixed solution;

[0018] S22. After the third mixed solution is cooled to 50-60°C under stirring, concentrated sulfuric acid (98% H2SO4) and benzoic acid (C7H6O2) are added, and the reaction time is 4-5h to obtain a fourth mixed solution;

[0019] S23. Add ethyl acetate to the fourth mixed solution for extraction, and subject the obtained modified molybdate-ethyl acetate mixed solution to high-temperature distillation at a distillation temperature of 150 to 180° C. to finally obtain pure modified molybdate.

[0020] Furthermore, the dispersion medium is a compound of poly-α-olefin (PAO), alkyl naphthalene (AN) and synthetic ester, and the weight ratio of poly-α-olefin (PAO), alkyl naphthalene (AN) and synthetic ester is (10-15):

[0021] (20~30):(4~8).

[0022] Furthermore, the carbon deposit cleaning agent is a compound of N-vinyl pyrrolidone (NVP), octadecyl methacrylate (SMA) and hexadecyl methacrylate (HMA), and the weight ratio of N-vinyl pyrrolidone (NVP), octadecyl methacrylate (SMA) and hexadecyl methacrylate (HMA) is (15-20): (5-10): (5-10).

[0023] Furthermore, the antioxidant is one or more of diphenylamine (DPA), 2,6-di-tert-butyl-p-cresol (BHT), N,N'-diphenyl-p-phenylenediamine (DPPD) and dithiocarbamate (DTDC).

[0024] Furthermore, the viscosity index improver is one or more of polyisobutylene, hydrogenated styrene-butadiene copolymer, polymethacrylate and styrene-isoprene copolymer.

[0025] On the other hand, based on the same inventive concept, the present invention also provides a method for preparing an engine lubricating protective agent containing flake graphite, which is applied to the engine lubricating protective agent containing flake graphite, comprising the following steps:

[0026] S31. Adding flake graphite to the kneader, adding carbon cleaning agent after kneading for 15 to 30 min, kneading for 1.5 to 2 h, kneading temperature 25 to 35 ° C, kneading speed 28 to 42 rpm / min, after kneading, grinding with a three-roll mill 4 to 6 times to obtain a fifth mixed solution;

[0027] S32. The fifth mixed solution is placed in a high-speed disperser and stirred, and modified boron nitride, modified molybdate, dispersion medium, antioxidant and viscosity index improver are added in sequence, the stirring speed is 1000 to 1200 rpm / min, and stirred for 4 to 6h to obtain a sixth mixed solution;

[0028] S33. Place the sixth mixed solution in a homogenizer, homogenize for 4 to 6 hours, and then filter it using a 5 to 10 μm filter. The oily substance obtained by filtration is the engine lubricating protective agent.

[0029] The mechanism of action of the above raw material components is as follows:

[0030] Flake graphite is a naturally occurring graphite form, consisting of many thin layers of graphite sheets, usually in the form of flakes, with a metallic luster. These graphite sheets are layered structures formed by carbon atoms arranged in a hexagonal honeycomb pattern. The graphite sheets interact with each other through van der Waals forces and are easy to peel off. In engine lubricant protectors, adding flake graphite can improve the lubrication performance of lubricants. Its layered structure can form a lubricating film on the metal surface, reduce direct contact between metals, reduce friction and wear, especially under high temperature and high pressure conditions. The layered structure of graphite can remain stable at high temperatures and is not easily oxidized, thus providing effective lubrication protection under extreme conditions; flake graphite can also enhance the thermal conductivity of lubricants, help dissipate heat, and reduce the operating temperature of mechanical parts; flake graphite is mainly composed of carbon atoms, and the chemical groups are relatively simple, mainly CC bonds and CH bonds, and the chemical properties are stable, which means that it will not chemically react with other components in the lubricant, ensuring the stability of the lubricant.

[0031] Boron nitride (BN) is an inorganic non-metallic material with a hexagonal crystal structure, similar to graphite, and has a layered structure similar to graphite, so it is also called "white graphite". The layered structure of boron nitride is connected by nitrogen atoms and boron atoms through covalent bonds, and the layers interact with each other through weak van der Waals forces; Boron nitride (especially cubic boron nitride) is a material with extremely high hardness and has a structure and properties similar to diamond. In the lubrication system, boron nitride particles play a supporting role and can remain stable under high temperature and high pressure conditions, and are not prone to deformation or wear. This stability of boron nitride can provide a mechanical support, so that the lubricating film can still maintain its structure without being destroyed when it is subjected to a large load. Modified boron nitride can be obtained by introducing siloxane groups (-Si(OR)3, where R is an alkyl or aryl group) on the surface of boron nitride through surface grafting modification, which can also reduce the friction coefficient of boron nitride and increase the resistivity of boron nitride. In the process of being applied to lubricating oil, the introduction of siloxane groups can improve the dispersibility of boron nitride in lubricating oil, making it more evenly distributed in the lubricating oil, thereby enhancing the lubrication effect; the siloxane groups can form a layer of organic silicon protective film on the metal surface, which can reduce direct contact between metals, reduce friction and wear, and thus reduce the friction coefficient; the introduction of siloxane groups can improve the thermal stability of boron nitride, and the siloxane groups form chemical bonds with the metal surface, thereby enhancing the adhesion and stability of the protective film, so that it can still maintain good lubrication properties in high temperature environments.

[0032] Molybdate (Mo(OR)n, where R represents an organic group and n is 3 or 6) is a class of organic compounds containing molybdenum. It plays the role of metal organic surfactant in engine lubricant protectors. Molybdate can form a protective film with the metal surface, reduce direct contact between metals, thereby reducing wear and preventing metal surface sintering. In addition, the antioxidant properties of molybdate can extend the service life of lubricants. By increasing the length of the molybdate molecule chain and introducing specific functional groups, such as carboxylic acid groups (-COOH), etc., the molecular structure of molybdate can be changed, and its solubility and dispersibility in lubricants can be optimized. The modified molybdate has better friction reduction and anti-wear properties. The modification can also further enhance the surface activity of the molybdate, making it more effective in reducing the surface tension of the lubricant. The modification can also improve the thermal stability of the molybdate, so that it can still maintain good performance under high temperature conditions, which helps heat conduction and maintains the fluidity of the lubricant.

[0033] Dispersion medium refers to a substance that can accommodate and stabilize the dispersed phase. In lubricating oil, the dispersion medium is usually a base oil, which can carry and disperse additives. To meet the long-term use requirements, the dispersion medium of the present invention is compounded with polyalphaolefin (PAO), alkylnaphthalene (AN) and synthetic ester. Polyalphaolefin has good thermal stability and oxidation stability. The long-chain alkyl in its molecular structure provides good lubricity. Alkylnaphthalene is a compound with an aromatic ring structure. The alkyl chain in its molecule provides hydrophobicity, and the aromatic ring provides a certain polarity, which helps to improve the solubility and dispersibility of oil products. Synthetic ester compounds usually have one or more ester groups (-COO-), which provide good polarity and oxidation stability, and also help to improve the low-temperature fluidity and biodegradability of oil products. According to the principle of similar dissolves, with the solubility of synthetic esters and alkylnaphthalene to polar substances, polyalphaolefin and various additives in lubricating oil are well dissolved, and the uniformity of oil products is maintained. At the same time, the intermolecular forces (such as van der Waals forces, hydrogen bonds, etc.) between various substances also help to stabilize the dispersed phase.

[0034] In the process of being applied to lubricating oil, the four substances of the present invention, namely, flake graphite, modified boron nitride, modified molybdate, and dispersion medium, play a role through a synergistic effect. The mechanical support of the modified boron nitride first supports the lamellar sliding structure of the flake graphite to form a stacked lubricating layer. Since both flake graphite and modified boron nitride are layered structures, the sliding action between layers enables the formation of a continuous lubricating film. Generally speaking, the particle size of ordinary graphite used in lubricating oil is generally 5 to 30 μm, and the thickness is 50 to 200 nm. However, if the particle size of graphite is too large and the size is too thick, it will be difficult for the graphite to be dispersed in the lubricating oil, forming an uneven lubricating film and resulting in a higher friction coefficient. The number of flake graphite particles increases, and the formed lubricating film is easy to precipitate and aggregate, thereby reducing the lubricating performance and service life. The particle size of the flake graphite used in the present invention is 0.5-1 μm and the thickness is 20-50 nm. Its excellent performance is specifically manifested in that the flake graphite and the modified boron nitride are more likely to interact with each other and the continuous lubricating film formed by the combination can be spread more evenly on the surface of the modified boron nitride. At the same time, the smaller particle size and thinner thickness of the flake graphite are also conducive to the dispersion and stability of the continuous lubricating film and are not easy to precipitate and aggregate. The small size and thin flaky structure of the flake graphite are also conducive to improving the thermal conductivity of the lubricating oil and helping to dissipate heat. Therefore, the existence of the continuous lubricating film is It can effectively reduce the friction coefficient, thereby reducing the friction resistance of the contact surface, and effectively improve the wear resistance of the lubricant; secondly, the modified molybdate makes the continuous lubricating film formed by the flake graphite and modified boron nitride more stably adhere to the metal surface through physical and chemical effects. The modified molybdate reduces the surface tension so that the lubricating film is evenly distributed on the metal surface, thereby forming a protective film on the metal surface. At the same time, the composite structure formed by the continuous lubricating film formed by the flake graphite and modified boron nitride and the interaction of the modified molybdate can effectively improve the fluidity of the lubricant and improve the thermal conductivity of the lubricant. At the same time, by increasing the specific surface area of ​​the continuous lubricating film, it can further improve the lubricant's wear resistance. Improving the heat transfer efficiency and accelerating the heat release of the friction surface will help reduce the temperature rise of the friction surface and reduce thermal damage, thereby maintaining the continuity and stability of the lubricating film; in addition, since the dispersion medium has good solubility and suspension ability, its polymer chain interacts with flake graphite, modified boron nitride, modified molybdate and other additives through physical adsorption and chemical action, further enhancing the dispersibility and stability of the lubricating oil. These substances significantly improve the lubricating performance of the lubricating oil through the synergistic effects of promoting the formation of a continuous lubricating film, enhancing the stability of the continuous lubricating film, promoting the uniform distribution of the continuous lubricating film, and enhancing heat conduction, wear resistance and dispersibility.

[0035] Carbon deposit cleaning agent is a chemical preparation used to remove carbon deposits inside equipment such as engines. The carbon deposit cleaning agent should have good dissolving ability, be able to dissolve and remove stubborn carbon deposits, and minimize corrosion to metal parts of the equipment while removing carbon deposits. The present invention uses N-vinyl pyrrolidone (NVP), octadecyl methacrylate (SMA) and hexadecyl methacrylate (HMA) as a carbon deposit cleaning agent. The pyrrolidone group in N-vinyl pyrrolidone has certain polarity and solubility. On the one hand, it can anchor with graphite particles to achieve a better dispersion effect, and on the other hand, it can anchor with carbon deposits to achieve a carbon deposit cleaning effect; the ester group (-COO-) in octadecyl methacrylate and methacrylic acid has certain lipophilicity, which can interact with the oily components in the carbon deposits to promote the dissolution and shedding of the carbon deposits. At the same time, the long-chain alkyl structure also helps to improve the compatibility and dispersibility of the cleaning agent in an oily environment.

[0036] Antioxidants are a class of chemical substances that can delay or prevent oxidation reactions of substances. In lubricating oils, the main function of antioxidants is to prevent the lubricating oil from oxidizing when it is exposed to high temperature, high pressure or oxygen, thereby extending the service life of the lubricating oil and protecting mechanical equipment. Antioxidants must have excellent antioxidant properties and thermal stability, be able to capture free radicals, prevent the chain oxidation reaction from proceeding, and maintain their antioxidant activity at high temperatures. Commonly used antioxidants include diphenylamine (DPA), 2,6-di-tert-butyl-p-cresol (BHT), N,N'-diphenyl-p-phenylenediamine (DPPD) and dithiocarbamate (DTDC). The amino groups (-NH2) in diphenylamine and N,N'-diphenyl-p-phenylenediamine can react with free radicals to form stable nitrogen-centered free radicals, thereby interrupting the oxidation chain reaction. The phenolic hydroxyl (-OH) groups in 2,6-di-tert-butyl-p-cresol can provide hydrogen atoms to react with free radicals to form stable phenoloxy free radicals, thereby preventing further oxidation reactions. The thiocarbamate groups in dithiocarbamates have strong sulfur free radical capture capabilities and can react with free radicals to form stable sulfur-centered free radicals, thereby inhibiting oxidation reactions. The synergistic effect of these chemical groups enables antioxidants to effectively protect lubricants from oxidative damage, maintain the performance of lubricants and the normal operation of mechanical equipment.

[0037] Viscosity index improver is an additive that can significantly improve the temperature-dependent viscosity characteristics of lubricating oils. Viscosity index improver should have excellent properties of increasing viscosity index, improving low-temperature fluidity and enhancing high-temperature stability. Common viscosity index improvers include polyisobutylene, hydrogenated styrene-butadiene copolymer, polymethacrylate and styrene-isoprene copolymer. At low temperatures, these polymer molecular chains curl, reducing the hindrance to the lubricant molecules, thereby reducing the viscosity. At high temperatures, the molecular chains stretch, increasing the hindrance to the lubricant molecules and increasing the viscosity. At the same time, the functional groups in these polymer molecules, such as the isobutylene group in polyisobutylene, the styrene and butadiene groups in hydrogenated styrene-butadiene copolymer, the methacrylate group in polymethacrylate, and the styrene and isoprene groups in styrene-isoprene copolymer can form intermolecular hydrogen bonds with the lubricant molecules, enhancing the intermolecular interactions and thus increasing the viscosity. At the same time, the presence of these polymer molecules will also occupy a certain space, hindering the free movement of the lubricant molecules, thereby increasing the viscosity. The characteristics and interactions of these chemical groups enable viscosity index improvers to effectively improve the viscosity characteristics of lubricants and improve their performance at different temperatures.

[0038] (3) Beneficial effects

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] 1. The mechanical support of modified boron nitride combines with the lamellar sliding structure of flake graphite to form a continuous lubricating film. The smaller particle size and thin flaky structure of flake graphite are superior, which is more likely to interact with modified boron nitride to form a continuous lubricating film and evenly spread on the surface of modified boron nitride.

[0041] 2. The modified molybdate ester forms a continuous lubricating film by physical adsorption and chemical action, which is stably attached to the metal surface to form a protective film. At the same time, the composite structure formed by the interaction between the continuous lubricating film and the modified molybdate ester effectively improves the fluidity of the lubricating oil and the heat conduction capacity. By increasing the specific surface area of ​​the continuous lubricating film, the heat transfer efficiency is further improved to reduce the thermal damage to the metal surface.

[0042] 3. The dispersion medium has good solubility and suspension ability. Its polymer chain further enhances the dispersibility and stability of the lubricating oil through physical adsorption and chemical reaction with flake graphite, modified boron nitride, modified molybdate and other additives;

[0043] 4. The four substances of flake graphite, modified boron nitride, modified molybdate and dispersion medium significantly improve the lubricating performance of lubricating oil by promoting the formation of continuous lubricating film, enhancing the stability of continuous lubricating film, promoting the uniform distribution of continuous lubricating film, and enhancing heat dissipation, wear resistance and dispersibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is the SEM image of flake graphite of Example 1 of the present invention;

[0045] Figure 2 This is the SEM image of the modified boron nitride of Example 1 of the present invention. DETAILED DESCRIPTION

[0046] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] The test equipment and preparations of the embodiments described below are as follows: electronic balance (Sartorius, Germany), electric constant temperature water bath (Jiangsu Kedao), electric blast drying oven (Wuxi Maruite), magnetic stirrer (Shanghai Meiyingpu), ultrasonic instrument (Shanghai Yixin), tubular furnace (Tianjin Bonare), scanning electron microscope (German Zeiss), kneading machine (Nantong Foster), high-speed disperser (Sichuan Ruitong), homogenizer (Shanghai Kaibaisi), four-ball friction and wear tester (Jinan Times Assay Tester), wear spot video measuring instrument (Jinan Times Assay Tester), HVU fully automatic kinematic viscosity tester (PAC, USA), lubricating oil foam property tester (Dalian Hongyuan Instrument), variable magnification stereo microscope (Olympus, Japan); steel balls were purchased from Shanghai Steel Ball Factory Co., Ltd., GCr15, and the steel ball diameter was 12.7 mm. Chemicals and reagents were purchased from Sigma-Aldrich.

[0048] Example 1

[0049] The present embodiment discloses an engine lubricating protective agent containing flake graphite, which is composed of the following raw materials in parts by weight: 8 parts of flake graphite, 4 parts of modified molybdate, 6 parts of dispersion medium, 3 parts of carbon deposit cleaning agent, 5 parts of antioxidant, and 2 parts of viscosity index improver; the flake graphite has a particle size of 0.5-1 μm and a thickness of 20-50 nm, the surface of the modified molybdate contains long-chain alkyl and carboxylic acid groups, and the engine lubricating protective agent also includes modified boron nitride, the modified boron nitride and flake graphite are in a weight ratio of 5:8, the friction coefficient of the modified boron nitride is 0.1-0.15, and the specific resistance is 10 6~10 8 Ω·cm and the modified boron nitride surface contains siloxane groups.

[0050] In the process of being applied to lubricating oil, the four substances, flake graphite, modified boron nitride, modified molybdate, and dispersion medium, work together through a synergistic effect. The structure of flake graphite is a layered structure formed by multiple layers of carbon atoms arranged in a hexagonal honeycomb, such as Figure 1 As shown in the figure, flake graphite has a layered structure. It can be seen with the naked eye that the layered structure is very thin and there are a lot of gaps between the structures. The interaction between these layers is weak. Therefore, when subjected to external force, the layers will slide relative to each other to produce a layered slip phenomenon. This layered slip phenomenon is the fundamental reason why flake graphite has good lubricity. Modified boron nitride is a material with extremely high hardness. It can remain stable under high temperature and high pressure conditions and is not prone to deformation and wear. The stability of modified boron nitride can provide a mechanical support. Modified boron nitride is combined with flake graphite through physical or chemical effects. There is van der Waals force between modified boron nitride and flake graphite, and the siloxane groups (-Si(OR)3), hydroxyl groups (-OH) and amino groups (-NH2) on the surface of modified boron nitride can form covalent bonds with carbon atoms on the surface of flake graphite to provide stronger bonding. These bonding effects enable modified boron nitride to provide more stable support for flake graphite, making it less likely for the graphite layer to be dislocated or damaged when under pressure. Therefore, the mechanical support of modified boron nitride first carries the lamellar slip structure of flake graphite to form a stacked lubricating layer. Since both flake graphite and modified boron nitride are layered structures, such as Figure 2As shown, the modified boron nitride also has a layered structure and is densely distributed. When the two surfaces contact each other and move relative to each other, the sliding effect between the layers causes a continuous lubricating film to be generated between the flake graphite and the modified boron nitride. Generally speaking, the particle size of ordinary graphite used in lubricating oil is generally 5 to 30 μm, and the thickness is 50 to 200 nm. However, if the particle size of the graphite is too large and the size is thick, it will be difficult for the graphite to be dispersed in the lubricating oil, forming an uneven lubricating film, resulting in a higher friction coefficient. At the same time, it will also make the formed lubricating film easy to precipitate and aggregate, thereby reducing the lubrication performance and service life. The particle size of the flake graphite used in the present invention is 0.5 to 1 μm and the thickness is 20 to 50 nm. Its excellent performance is specifically manifested in the smaller particle size and thinner thickness, which makes it easier for the flake graphite and the modified boron nitride to interact with each other and the continuous lubricating film formed by the combination can be spread more evenly on the surface of the modified boron nitride. At the same time, the smaller particle size and thinner thickness of the flake graphite The thickness of the continuous lubricating film is also helpful for the dispersion and stability of the continuous lubricating film and is not easy to precipitate and aggregate. This is because when the particle size is small and the thickness is thin, the number of particles between the flake graphite and the modified boron nitride increases, thereby providing more contact area in the same volume. The smaller particle size also increases the surface energy of the flake graphite particles, making it easier for the flake graphite and the modified boron nitride to undergo physical adsorption and chemical bonding, which helps to form a stable continuous lubricating film. The smaller particle size and flaky structure of the flake graphite also help to improve the thermal conductivity of the lubricating oil and help dissipate heat. The presence of the continuous lubricating film can fill the microscopic uneven structure of the surface and effectively reduce the friction coefficient. As shown in Table 1, the friction coefficient of the modified boron nitride is 0.1 to 0.15, but the combined effect of the flake graphite and the modified boron nitride reduces the friction coefficient of the lubricating oil to below 0.1, which effectively reduces the friction resistance of the contact surface and thereby improves the wear resistance of the lubricating oil. Modified molybdates make the continuous lubricating film formed by the combined action of flake graphite and modified boron nitride stably adhere to the metal surface through physical and chemical effects. This is because the carboxyl (-COOH) hydrophilic group in the modified molybdate molecule tends to interact with the oxide layer on the metal surface to form intermolecular hydrogen bonds, while the alkyl (-CH3, -CH2CH3, etc.) and aryl (-C6H5) lipophilic groups interact with the flake graphite or modified boron nitride in the continuous lubricating film through van der Waals forces, so that the continuous lubricating film is stably attached to the metal surface. At the same time, since the modified molybdate plays a role in reducing the surface tension in the lubricating oil, the liquid is more likely to spread on the metal surface to form a uniform lubricating film, so that the continuous lubricating film is attached to the metal surface to form a protective film. This protective film can effectively prevent the metal from directly contacting the external environment and reduce corrosion and wear on the metal surface.At the same time, the continuous lubricating film formed by the interaction of flake graphite and modified boron nitride and the composite structure formed by the interaction of modified molybdate ester can effectively reduce the pour point of the lubricant (i.e., the lowest temperature at which the lubricant can still flow). Because the modified molybdate ester contains long-chain alkyl groups, the modified molybdate ester acts as a "carrier" to carry the continuous lubricating film to move together, thereby effectively improving the fluidity of the lubricant, allowing the lubricant to flow more easily between the friction surfaces, thereby taking away more heat and improving the thermal conductivity of the lubricant. At the same time, the formation of the composite structure can increase the specific surface area of ​​the continuous lubricating film and thus improve the heat transfer efficiency, which further accelerates the heat release of the friction surface, helps to reduce the temperature rise of the friction surface, reduces thermal damage, and allows heat to be more effectively transferred from the friction surface to the lubricant, thereby protecting the friction surface from high temperature damage and maintaining the continuity and stability of the lubricating film. The role of the dispersion medium in lubricating oil is mainly achieved through the physical and chemical effects between its polymer chain and lubricating additives. According to the principle of like dissolves like, dispersion media such as poly-α-olefins, alkyl naphthalene and synthetic esters have good solubility and can effectively dissolve various additives in lubricating oil, including flake graphite, modified boron nitride, modified molybdate, etc. When the dispersion medium contacts solid particles such as flake graphite and modified boron nitride, the polar groups in the dispersion medium will combine with the polar groups on the surface of the solid particles through physical effects such as hydrogen bonds and van der Waals forces. The hydroxyl (-OH) in the dispersion medium will form intermolecular hydrogen bonds with the hydroxyl (-OH) or carboxyl (-COOH) on the surface of the solid particles, thereby enhancing the suspension ability of the solid particles in the lubricating oil. The carboxyl (-COOH) in the dispersion medium will also undergo esterification reaction with the hydroxyl (-OH) on the surface of the solid particles to form a stable ester bond (-COO-). At the same time, the polymer chains in the dispersion medium can also increase the distance between molecules through entanglement, thereby improving suspension and dispersibility. The long-chain alkyl in the dispersion medium can interact with the lipophilic groups such as alkyl (-CH3, -CH2CH3, etc.) and aryl (-C6H5) in the modified molybdate, further increasing the dispersibility and stability of the lubricating oil. Flake graphite, modified boron nitride, modified molybdate, and dispersion media significantly improve the lubricating properties of lubricating oils through their synergistic effects in promoting the formation of continuous lubricating films, enhancing the stability of continuous lubricating films, promoting the uniform distribution of continuous lubricating films, and enhancing heat dissipation, wear resistance, and dispersibility. At the same time, they also meet the needs of green environmental development and are environmentally friendly.

[0051] The preparation method of the modified boron nitride comprises:

[0052] S11. Under ultrasonic conditions, boron nitride is added to an aqueous sodium hydroxide solution at an ultrasonic frequency of 40 to 50 kHz, and heated in a water bath at a heating temperature of 70 to 80° C. for a reaction time of 4 to 6 hours to obtain a first mixed solution;

[0053] S12. Adding silane coupling agent KH-570 and anhydrous ethanol to the first mixed solution in sequence under stirring, heating to 50 to 60° C., stirring for 3 to 4 hours until the reaction is sufficient to obtain a second mixed solution;

[0054] S13. The second mixed solution is allowed to stand for 8 to 10 hours, followed by solid-liquid separation, and the obtained precipitate is dried at a temperature of 90 to 120°C for 12 to 15 hours. After drying, it is vacuum calcined at a heating rate of 5 to 10°C / min, at a temperature of 400 to 500°C, and for 3 to 4 hours. The obtained solid is the modified boron nitride.

[0055] The preparation method of the modified molybdate comprises:

[0056] S21. While stirring, add molybdic acid (H2MoO4) to anhydrous ethanol and stir for 1 to 2 hours to fully dissolve it. Heat it to 80 to 100°C in a water bath and then add concentrated sulfuric acid (98% H2SO4) and octanol (C8H 17 OH) for esterification reaction for 8 to 10 hours to obtain a third mixed solution;

[0057] S22. After the third mixed solution is cooled to 50-60°C under stirring, concentrated sulfuric acid (98% H2SO4) and benzoic acid (C7H6O2) are added, and the reaction time is 4-5h to obtain a fourth mixed solution;

[0058] S23. Add ethyl acetate to the fourth mixed solution for extraction, and subject the obtained modified molybdate-ethyl acetate mixed solution to high-temperature distillation at a distillation temperature of 150 to 180° C. to finally obtain pure modified molybdate.

[0059] The dispersion medium is a compound of polyalphaolefin (PAO), alkylnaphthalene (AN) and synthetic ester, and the weight ratio of polyalphaolefin (PAO), alkylnaphthalene (AN) and synthetic ester is (10-15): (20-30): (4-8).

[0060] The carbon deposit cleaning agent is a compound of N-vinyl pyrrolidone (NVP), octadecyl methacrylate (SMA) and hexadecyl methacrylate (HMA), wherein the weight ratio of N-vinyl pyrrolidone (NVP), octadecyl methacrylate (SMA) and hexadecyl methacrylate (HMA) is (15-20): (5-10): (5-10).

[0061] The antioxidant is one or more of diphenylamine (DPA), 2,6-di-tert-butyl-p-cresol (BHT), N,N'-diphenyl-p-phenylenediamine (DPPD) and dithiocarbamate (DTDC).

[0062] The viscosity index improver is one or more of polyisobutylene, hydrogenated styrene-butadiene copolymer, polymethacrylate and styrene-isoprene copolymer.

[0063] A method for preparing an engine lubricating protective agent containing flake graphite, which is applied to the engine lubricating protective agent containing flake graphite, comprises the following steps:

[0064] S31. Adding flake graphite to the kneader, adding carbon cleaning agent after kneading for 15 to 30 min, kneading for 1.5 to 2 h, kneading temperature 25 to 35 ° C, kneading speed 28 to 42 rpm / min, after kneading, grinding with a three-roll mill 4 to 6 times to obtain a fifth mixed solution;

[0065] S32. The fifth mixed solution is placed in a high-speed disperser and stirred, and modified boron nitride, modified molybdate, dispersion medium, antioxidant and viscosity index improver are added in sequence, the stirring speed is 1000 to 1200 rpm / min, and stirred for 4 to 6h to obtain a sixth mixed solution;

[0066] S33. Place the sixth mixed solution in a homogenizer, homogenize for 4 to 6 hours, and then filter it using a 5 to 10 μm filter. The oily substance obtained by filtration is the engine lubricating protective agent.

[0067] Example 2

[0068] The present embodiment discloses an engine lubricating protective agent containing flake graphite, which is composed of the following raw materials in parts by weight: 5 parts of flake graphite, 2 parts of modified molybdate, 4 parts of dispersion medium, 1 part of carbon deposit cleaning agent, 2 parts of antioxidant, and 1 part of viscosity index improver; the flake graphite has a particle size of 0.5-1 μm and a thickness of 20-50 nm, the surface of the modified molybdate contains long-chain alkyl and carboxylic acid groups, and the engine lubricating protective agent also includes modified boron nitride, the modified boron nitride and flake graphite are in a weight ratio of 5:5, the friction coefficient of the modified boron nitride is 0.1-0.15, and the specific resistance is 10 6 ~10 8 Ω·cm and the modified boron nitride surface contains siloxane groups.

[0069] The preparation methods of the modified boron nitride and the modified molybdate in this embodiment are the same as those in Example 1. The preparation method of an engine lubricating protective agent containing flake graphite in this embodiment is the same as that in Example 1.

[0070] Example 3

[0071] The present embodiment discloses an engine lubricating protective agent containing flake graphite, which is composed of the following raw materials in parts by weight: 10 parts of flake graphite, 6 parts of modified molybdate, 8 parts of dispersion medium, 5 parts of carbon deposit cleaning agent, 8 parts of antioxidant, and 4 parts of viscosity index improver; the flake graphite has a particle size of 0.5-1 μm and a thickness of 20-50 nm, the surface of the modified molybdate contains long-chain alkyl and carboxylic acid groups, and the engine lubricating protective agent also includes modified boron nitride, the modified boron nitride and flake graphite are in a weight ratio of 5:10, the friction coefficient of the modified boron nitride is 0.1-0.15, and the specific resistance is 10 6 ~10 8 Ω·cm and the modified boron nitride surface contains siloxane groups.

[0072] The preparation methods of the modified boron nitride and the modified molybdate in this embodiment are the same as those in Example 1. The preparation method of an engine lubricating protective agent containing flake graphite in this embodiment is the same as that in Example 1.

[0073] Example 4

[0074] The present embodiment discloses an engine lubricating protective agent containing flake graphite, which is composed of the following raw materials in parts by weight: 8 parts of flake graphite, 5 parts of modified molybdate, 6 parts of dispersion medium, 2 parts of carbon deposit cleaning agent, 5 parts of antioxidant, and 2 parts of viscosity index improver; the flake graphite has a particle size of 0.5-1 μm and a thickness of 20-50 nm, the surface of the modified molybdate contains long-chain alkyl and carboxylic acid groups, and the engine lubricating protective agent also includes modified boron nitride, the modified boron nitride and flake graphite are in a weight ratio of 5:8, the friction coefficient of the modified boron nitride is 0.1-0.15, and the specific resistance is 10 6 ~10 8 Ω·cm and the modified boron nitride surface contains siloxane groups.

[0075] The preparation methods of the modified boron nitride and the modified molybdate in this embodiment are the same as those in Example 1. The preparation method of an engine lubricating protective agent containing flake graphite in this embodiment is the same as that in Example 1.

[0076] Example 5

[0077] The present embodiment discloses an engine lubricating protective agent containing flake graphite, which is composed of the following raw materials in parts by weight: 8 parts of flake graphite, 3 parts of modified molybdate, 5 parts of dispersion medium, 2 parts of carbon deposit cleaning agent, 5 parts of antioxidant, and 2 parts of viscosity index improver; the flake graphite has a particle size of 0.5-1 μm and a thickness of 20-50 nm, the surface of the modified molybdate contains long-chain alkyl and carboxylic acid groups, and the engine lubricating protective agent also includes modified boron nitride, the modified boron nitride and flake graphite are in a weight ratio of 5:8, the friction coefficient of the modified boron nitride is 0.1-0.15, and the specific resistance is 106 ~10 8 Ω·cm and the modified boron nitride surface contains siloxane groups.

[0078] The preparation methods of the modified boron nitride and the modified molybdate in this embodiment are the same as those in Example 1. The preparation method of an engine lubricating protective agent containing flake graphite in this embodiment is the same as that in Example 1.

[0079] Control group 1

[0080] The difference between this embodiment and embodiment 1 is that flake graphite is not contained.

[0081] This embodiment discloses an engine lubricating protective agent containing flake graphite, which is composed of the following raw materials in parts by weight: 4 parts of modified molybdate, 6 parts of dispersion medium, 3 parts of carbon deposit cleaning agent, 5 parts of antioxidant, and 2 parts of viscosity index improver; the surface of the modified molybdate contains long-chain alkyl and carboxylic acid groups, and the engine lubricating protective agent also includes 5 parts of modified boron nitride, the friction coefficient of the modified boron nitride is 0.1-0.15, and the specific resistance is 10 6 ~10 8 Ω·cm and the modified boron nitride surface contains siloxane groups.

[0082] The preparation methods of the modified boron nitride and the modified molybdate in this embodiment are the same as those in Example 1. The preparation method of an engine lubricating protective agent containing flake graphite in this embodiment is the same as that in Example 1.

[0083] Control group 2

[0084] The difference between this embodiment and embodiment 1 is that modified boron nitride is not contained.

[0085] The present embodiment discloses an engine lubricating protective agent containing flake graphite, which is composed of the following raw materials in parts by weight: 8 parts of flake graphite, 4 parts of modified molybdate, 6 parts of dispersion medium, 3 parts of carbon deposit cleaning agent, 5 parts of antioxidant, and 2 parts of viscosity index improver; the flake graphite has a particle size of 0.5 to 1 μm and a thickness of 20 to 50 nm, and the surface of the modified molybdate contains long-chain alkyl and carboxylic acid groups.

[0086] The preparation method of the modified molybdate ester in this embodiment is consistent with that in Example 1. The preparation method of an engine lubricating protective agent containing flake graphite in this embodiment is consistent with that in Example 1.

[0087] Control group 3

[0088] The difference between this embodiment and embodiment 1 is that the modified molybdate is not contained.

[0089] The present embodiment discloses an engine lubricating protective agent containing flake graphite, which is composed of the following raw materials in parts by weight: 8 parts of flake graphite, 6 parts of dispersion medium, 3 parts of carbon deposit cleaning agent, 5 parts of antioxidant, and 2 parts of viscosity index improver; the flake graphite has a particle size of 0.5-1 μm and a thickness of 20-50 nm, and the engine lubricating protective agent also includes modified boron nitride, the modified boron nitride and flake graphite are in a weight ratio of 5:8, the friction coefficient of the modified boron nitride is 0.1-0.15, and the specific resistance is 10 6 ~10 8 Ω·cm and the modified boron nitride surface contains siloxane groups.

[0090] The preparation method of the modified boron nitride in this embodiment is consistent with that in Example 1. The preparation method of an engine lubricating protective agent containing flake graphite in this embodiment is consistent with that in Example 1.

[0091] Control group 4

[0092] The difference between this embodiment and embodiment 1 is that no dispersion medium is contained.

[0093] The present embodiment discloses an engine lubricating protective agent containing flake graphite, which is composed of the following raw materials in parts by weight: 8 parts of flake graphite, 4 parts of modified molybdate, 3 parts of carbon deposit cleaning agent, 5 parts of antioxidant, and 2 parts of viscosity index improver; the flake graphite has a particle size of 0.5-1 μm and a thickness of 20-50 nm, the surface of the modified molybdate contains long-chain alkyl and carboxylic acid groups, and the engine lubricating protective agent also includes modified boron nitride, the modified boron nitride and flake graphite are in a weight ratio of 5:8, the friction coefficient of the modified boron nitride is 0.1-0.15, and the specific resistance is 10 6 ~10 8 Ω·cm and the modified boron nitride surface contains siloxane groups.

[0094] The preparation methods of the modified boron nitride and the modified molybdate in this embodiment are the same as those in Example 1. The preparation method of an engine lubricating protective agent containing flake graphite in this embodiment is the same as that in Example 1.

[0095] Control group 5

[0096] The difference between this embodiment and embodiment 1 is that no carbon deposit cleaning agent is included.

[0097] The present embodiment discloses an engine lubricating protective agent containing flake graphite, which is composed of the following raw materials in parts by weight: 8 parts of flake graphite, 4 parts of modified molybdate, 6 parts of dispersion medium, 5 parts of antioxidant, and 2 parts of viscosity index improver; the flake graphite has a particle size of 0.5-1 μm and a thickness of 20-50 nm, the surface of the modified molybdate contains long-chain alkyl and carboxylic acid groups, and the engine lubricating protective agent also includes modified boron nitride, the modified boron nitride and flake graphite are in a weight ratio of 5:8, the friction coefficient of the modified boron nitride is 0.1-0.15, and the specific resistance is 10 6 ~10 8 Ω·cm and the modified boron nitride surface contains siloxane groups.

[0098] The preparation methods of the modified boron nitride and the modified molybdate in this embodiment are the same as those in Example 1. The preparation method of an engine lubricating protective agent containing flake graphite in this embodiment is the same as that in Example 1.

[0099] Control group 6

[0100] The difference between this embodiment and embodiment 1 is that no antioxidant is contained.

[0101] The present embodiment discloses an engine lubricating protective agent containing flake graphite, which is composed of the following raw materials in parts by weight: 8 parts of flake graphite, 4 parts of modified molybdate, 6 parts of dispersion medium, 3 parts of carbon deposit cleaning agent, and 2 parts of viscosity index improver; the flake graphite has a particle size of 0.5-1 μm and a thickness of 20-50 nm, the surface of the modified molybdate contains long-chain alkyl and carboxylic acid groups, and the engine lubricating protective agent also includes modified boron nitride, the modified boron nitride and flake graphite are in a weight ratio of 5:8, the friction coefficient of the modified boron nitride is 0.1-0.15, and the specific resistance is 10 6 ~10 8 Ω·cm and the modified boron nitride surface contains siloxane groups.

[0102] The preparation methods of the modified boron nitride and the modified molybdate in this embodiment are the same as those in Example 1. The preparation method of an engine lubricating protective agent containing flake graphite in this embodiment is the same as that in Example 1.

[0103] Control group 7

[0104] The difference between this embodiment and embodiment 1 is that no viscosity index improver is contained.

[0105] The present embodiment discloses an engine lubricating protective agent containing flake graphite, which is composed of the following raw materials in parts by weight: 8 parts of flake graphite, 4 parts of modified molybdate, 6 parts of dispersion medium, 3 parts of carbon deposit cleaning agent, and 5 parts of antioxidant; the flake graphite has a particle size of 0.5-1 μm and a thickness of 20-50 nm, the surface of the modified molybdate contains long-chain alkyl and carboxylic acid groups, and the engine lubricating protective agent also includes modified boron nitride, the modified boron nitride and flake graphite are in a weight ratio of 5:8, the friction coefficient of the modified boron nitride is 0.1-0.15, and the specific resistance is 10 6 ~10 8 Ω·cm and the modified boron nitride surface contains siloxane groups.

[0106] The preparation methods of the modified boron nitride and the modified molybdate in this embodiment are the same as those in Example 1. The preparation method of an engine lubricating protective agent containing flake graphite in this embodiment is the same as that in Example 1.

[0107] Effect evaluation: The engine lubricating protective agent prepared in each experimental group was added to the plant base oil to obtain the lubricating oil of each experimental group. The plant base oil was a compound of castor oil and palm oil. The volume ratio of the plant base oil to the engine lubricating protective agent was 5:1. The following properties were tested for the lubricating oil of each experimental group. Friction performance test: The four-ball friction and wear test was carried out according to SH / T 0189-2017 "Determination of the anti-wear performance of lubricating oil by four-ball method". Before the test, the steel balls, fixtures and oil box were cleaned with petroleum ether for 3 times, and 3 lower steel balls were loaded into the oil box. The test oil was poured into the oil box until it exceeded the top of the ball by 3mm, and the upper steel ball was clamped with a fixture. During the test, the lower 3 steel balls were fixed, and the upper steel ball rotated under the drive of the motor. The test conditions were: speed 1200±60rpm, load 392±2N, temperature 75±2℃, and friction time 60±1min. After the friction experiment, remove the lower steel ball, pour out the lubricating oil, observe the wear spots with an optical microscope, test the diameters of the wear spots formed on the three steel balls from two directions perpendicular to each other, take the average of the six wear spot diameters as the wear spot diameter, and obtain the friction coefficient after the experiment.

[0108] Stability test: The stability test was carried out on the lubricating oil in each experimental group. 100 mL of lubricating oil was placed in a beaker for 30 days of static observation. The dispersion and stability of the lubricating oil were determined by the percentage of the bottom sediment powder volume to the total added powder volume. The smaller the percentage of the sediment powder volume, the better the dispersion stability of the lubricating oil, and vice versa. The upper layer of oil was taken every 10 days and the absorbance value was measured with a spectrophotometer to evaluate the dispersion stability of the lubricating oil.

[0109] Table 1 Friction performance and dispersion stability performance results of the lubricating oils obtained in each experimental group

[0110]

[0111] The friction performance and dispersion stability performance results of the lubricating oils obtained in each experimental group are shown in Table 1. The average friction coefficient of the lubricating oil in Example 1 is the smallest at 0.078, and the wear spot diameter is also the smallest at 542 μm. It can be seen that the lubricating oil exhibits excellent wear reduction performance. By comparing the average friction coefficients and wear spot diameters of Example 1 with those of the experimental groups of Control Group 1, Control Group 2, Control Group 3 and Control Group 4, it can be found that when the lubricating protective agent contains four substances, namely flake graphite, modified boron nitride, modified molybdate and dispersion medium, the average friction coefficient and wear spot diameter of the lubricating oil can be greatly reduced, thereby improving the lubricating performance of the lubricating oil. For example, the lubricating oils prepared in Examples 2, 3, 4 and 5, although the raw material formula used in preparing the lubricating protective agent is not the most preferred, the average friction coefficient and wear spot diameter of each group of lubricating oil are smaller than the average friction coefficient and wear spot diameter of the experimental groups of Control Group 1, Control Group 2, Control Group 3 and Control Group 4.

[0112] From the results of the stability test, compared with the control group 1 without flake graphite, the control group 2 without modified boron nitride, the control group 3 without modified molybdate, and the control group 4 without dispersion medium, the dispersion stability of the lubricating oil prepared by the other experimental groups is better than these control groups, which is specifically manifested in that the volume percentage of the bottom sedimentation powder of the lubricating oil is small and the absorbance value is relatively stable during the test period, and the value has no obvious fluctuation. On the contrary, the volume percentage of the bottom sedimentation powder of the control group 1, the control group 2, the control group 3 and the control group 4 experimental groups reached 7% at most, and the absorbance value showed obvious large fluctuations, indicating that the dispersion stability is not good. It also further shows that the simultaneous presence of flake graphite, modified boron nitride, modified molybdate and dispersion medium in the engine lubricating protective agent and their use in the lubricating oil can significantly enhance the friction performance and dispersion stability of the lubricating oil, thereby improving the lubricating performance of the lubricating oil. Through the above effective tests, the engine lubricating protective agent containing flake graphite in Example 1 of the present invention is added to the plant base oil to prepare the lubricating oil, which has a significant effect, can effectively enhance the lubricating performance and environmental friendliness of the lubricating oil, improve engine power and reduce fuel and oil consumption, protect the engine by reducing wear and corrosion, enhance heat dissipation performance, extend the service life of the engine, and meet the needs of environmentally friendly green development.

[0113] Finally, it should be noted that: Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An engine lubricating protective agent containing flake graphite, characterized in that: The invention is composed of the following raw materials in parts by weight: 5-10 parts of flake graphite, 2-6 parts of modified molybdate, 4-8 parts of dispersion medium, 1-5 parts of carbon deposit cleaning agent, 2-8 parts of antioxidant, and 1-4 parts of viscosity index improver; The flake graphite has a particle size of 0.5-1 μm and a thickness of 20-50 nm; The modified molybdate surface contains long-chain alkyl and carboxylic acid groups; The engine lubricating protective agent also includes: Modified boron nitride; The modified boron nitride and flake graphite are in a weight ratio of 5:(5-10); The friction coefficient of the modified boron nitride is 0.1-0.15, and the specific resistance is 10 6 ~10 8 Ω·cm and the surface of modified boron nitride contains siloxane groups; The preparation method of the modified boron nitride comprises: S11. Adding boron nitride to an aqueous sodium hydroxide solution under ultrasound, with an ultrasound frequency of 40 to 50 kHz, and heating in a water bath at a temperature of 70 to 80° C. for a reaction time of 4 to 6 hours to obtain a first mixed solution; S12. Adding silane coupling agent KH-570 and anhydrous ethanol to the first mixed solution in sequence under stirring, heating to 50-60° C., stirring for 3-4 h until fully reacted, to obtain a second mixed solution; S13. The second mixed solution was allowed to stand for 8 to 10 hours, and then the solid-liquid separation was performed. The precipitate was dried at a temperature of 90 to 120°C for 12 to 15 hours. After drying, the precipitate was vacuum calcined at a heating rate of 5 to 10°C / min, a calcination temperature of 400 to 500°C, and a calcination time of 3 to 4 hours. The solid obtained was modified boron nitride. The preparation method of the modified molybdate comprises: S21. Add molybdic acid (H2MoO4) to anhydrous ethanol under stirring and stir for 1-2 hours to fully dissolve it. Heat it to 80-100°C in a water bath and then add concentrated sulfuric acid and octanol (C8H 17 OH) for esterification reaction for 8 to 10 hours to obtain a third mixed solution; S22. After the third mixed solution is cooled to 50-60°C under stirring, concentrated sulfuric acid and benzoic acid (C7H6O2) are added, and the reaction time is 4-5h to obtain a fourth mixed solution; S23. Ethyl acetate was added to the fourth mixed solution for extraction, and the modified molybdate ester - ethyl acetate mixture obtained by extraction was distilled at high temperature, the distillation temperature was 150 ~ 180 ℃, and finally a pure modified molybdate ester was obtained; The dispersion medium is a compound of poly-α-olefin (PAO), alkyl naphthalene (AN) and synthetic ester, and the weight ratio of poly-α-olefin (PAO), alkyl naphthalene (AN) and synthetic ester is (10-15): (20-30): (4-8); The carbon deposit cleaning agent is a compound of N-vinyl pyrrolidone (NVP), octadecyl methacrylate (SMA) and hexadecyl methacrylate (HMA), wherein the weight ratio of N-vinyl pyrrolidone (NVP), octadecyl methacrylate (SMA) and hexadecyl methacrylate (HMA) is (15-20): (5-10): (5-10).

2. The engine lubricating protective agent containing flake graphite according to claim 1, characterized in that: The antioxidant is one or more of diphenylamine (DPA), 2,6-di-tert-butyl-p-cresol (BHT), N,N'-diphenyl-p-phenylenediamine (DPPD) and dithiocarbamate (DTDC).

3. The engine lubricating protective agent containing flake graphite according to claim 1, characterized in that: The viscosity index improver is one or more of polyisobutylene, hydrogenated styrene-butadiene copolymer, polymethacrylate and styrene-isoprene copolymer.

4. A method for preparing an engine lubricating protective agent containing flake graphite, which is used to prepare the engine lubricating protective agent as claimed in any one of claims 1 to 3, characterized in that: The method comprises the following steps: S31. Adding flake graphite to the kneader, adding carbon cleaning agent after kneading for 15 to 30 min, kneading for 1.5 to 2 h, kneading temperature 25 to 35 ° C, kneading speed 28 to 42 rpm, after kneading, grinding with a three-roll mill 4 to 6 times to obtain a fifth mixed solution; S32. The fifth mixed solution was placed in a high-speed disperser and stirred, and modified boron nitride, modified molybdate, dispersion medium, antioxidant and viscosity index improver were added successively, and the stirring speed was 1000 to 1200 rpm, and stirred for 4 to 6h to obtain a sixth mixed solution; S33. Place the sixth mixed solution in a homogenizer, homogenize for 4 to 6 hours, and then filter it using a 5 to 10 μm filter. The oily substance obtained by filtration is the engine lubricating protective agent.

Citation Information

Patent Citations

  • Lubricant having nanoparticles and microparticles to enhance fuel efficiency, and a laser synthesis method to create dispersed nanoparticles

    CN101842470A

  • Wide-temperature-range biolubricant for vehicle and preparation method of wide-temperature-range biolubricant

    CN105950266A